(untitled) (Global Journal of Management and Business Research, 2013)
Sustainability is a crucial issue for corporate world today. The interest of investors in Socially Responsible Investment (SRI) has grown substantially over last decade. Thus, sustainability has potential to influence company performance. The purpose of this paper is to find "whether sustainable companies are more profitable". Various researches were conducted in past for examining this relationship. Results, however, have been mixed and inconclusive. Moreover, most of the studies have been conducted in context of developed countries. The purpose of this paper is to examine impact of sustainability rating of company on its financial performance in an Indian context using secondary data. We also separately analyze impact of four key components of sustainability (i.e. Community, Employees, Environment and Governance) on financial performance. We find no significant association between overall sustainability rating and financial performance. However, further analysis reveals that four components of sustainability have significant but varying impact on financial performance.